2014
DOI: 10.1136/gutjnl-2014-307748
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic upregulation of metabotropic glutamate receptor 2 in the spinal cord attenuates oestrogen-induced visceral hypersensitivity

Abstract: Objective Epigenetic mechanisms are potential targets to relieve somatic pain. However, little is known whether epigenetic regulation interferes with visceral pain. Previous studies show that estrogen facilitates visceral pain. This study aimed to determine if histone hyperacetylation in the spinal cord could attenuate estrogen facilitated visceral pain. Design The effect of the histone deacetylase (HDAC) inhibitor suberoylanilide hydroxamic acid (SAHA) on the magnitude of the visceromotor response (VMR) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 32 publications
3
53
1
Order By: Relevance
“…In addition, SAHA up-regulated the expression of mGlu2 receptors in the DRG, which was associated with increased acetylation of p65/RelA (Chiechio et al, 2009). Interestingly, data consistent with these observations were also recently reported in a rat model of estrogen-induced visceral hypersensitivity (Cao et al, 2014). In addition, Bai et al found that pre-injection of SAHA (1 = 25 g, intrathecal) significantly delayed the thermal hyperalgesia induced by unilateral CFA injection in the hind paw and that intrathecal injection with 25 g of SAHA attenuated existing thermal hyperalgesia 24 h after CFA injection.…”
Section: Hydroxamatessupporting
confidence: 68%
“…In addition, SAHA up-regulated the expression of mGlu2 receptors in the DRG, which was associated with increased acetylation of p65/RelA (Chiechio et al, 2009). Interestingly, data consistent with these observations were also recently reported in a rat model of estrogen-induced visceral hypersensitivity (Cao et al, 2014). In addition, Bai et al found that pre-injection of SAHA (1 = 25 g, intrathecal) significantly delayed the thermal hyperalgesia induced by unilateral CFA injection in the hind paw and that intrathecal injection with 25 g of SAHA attenuated existing thermal hyperalgesia 24 h after CFA injection.…”
Section: Hydroxamatessupporting
confidence: 68%
“…In this regard Ralya and McCarson (Ralya and McCarson, 2014) showed that a surge in serum estrogen can produce a stimulus-intensity-dependent increase in inflammation-evoked nociceptive behavior, which is consistent with the findings of Lu and coworkers (Lu et al, 2012) showing that systemic application of estriol, as well as 17β-estradiol (E 2 ), increases hyperalgesia in CFA-induced chronic pain. In addition, (Zhang et al, 2012) showed that spinal administration of E 2 produces mechanical allodynia and thermal hyperalgesia in both male and female rats confirming the local spinal effect of E 2 , while Cao et al (Cao et al, 2014) demonstrated that spinal E 2 facilitates the visceromotor response to colorectal distention.…”
Section: Discussionmentioning
confidence: 90%
“…104 Another estrogenmediated mechanism that could drive visceral hypersensitivity is via the induction of µ-opioid receptor internalization within the medial preoptic nucleus and the posterodorsal medial amygdala. 105 At the level of the spinal cord, multiple studies have characterized estrogen as an important modulator of visceral nociceptive signaling, specifically through an effect on the N-methyl-D-aspartate receptor, 106 metabotropic glutamate receptor 2 (mGluR2), 107 and ionotropic glutamate receptor subunit 2B activity 108 within the spinal cord.…”
Section: Sex Linked Differences In Visceral Sensitivitymentioning
confidence: 99%
“…127 Furthermore, in a model of visceral hypersensitivity induced by 17β-estradiol in female rats, SAHA infused on to the lumbosacral spinal cord lead to hyperacetylation of H3K9 at the promoter for the metabotropic glutamate receptor-2 (mGLuR2). 107 Counter intuitively, the SAHA-induced increase in mGluR2 expression inhibited the estradiol-induced visceral hypersensitivity. 107 Evidence from models of chronic cystitis or esophageal reflux disease identified several miRNAs associated with chronic visceral pain.…”
Section: Epigenetic Mechanisms That Contribute To Irritable Bowel Synmentioning
confidence: 99%
See 1 more Smart Citation